Ceramic dressing, tab, battery cell, battery and electric equipment

By using modified polyacrylic acid materials as the binder, the ceramic dressing improves adhesion and adaptability in the extreme ear ceramic coating, solves the problems of bond strength attenuation and laser die-cutting abnormalities, and achieves better electrolyte resistance and laser die-cutting effect.

CN119752261APending Publication Date: 2025-04-04BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411551446.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The bond strength of the extreme ear ceramic coating is attenuated during the battery cell manufacturing process, has poor adaptability, is prone to wrinkles or falls off, and abnormalities such as ceramic welding slag and molten beads are easily found during the laser die cutting process.

Method used

Modified polyacrylic acid materials with specific structures are used as the binder, and ceramic dressings are highly adaptable to different electrolyte systems, which can effectively improve problems such as laser die-cutting and molten beads.

Benefits of technology

The adhesion force of the ceramic dressing increases, reducing the use of adhesive, improving the electrolyte resistance and adaptability of the extreme ear ceramic coating, and effectively improving the laser die-cutting effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752261A_ABST
    Figure CN119752261A_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic dressing, a tab, a battery cell, a battery and electric equipment, the ceramic dressing comprises a binder, the binder comprises a compound represented by a chemical structure general formula (1): # imgabs 0 # formula (1), in the formula (1), R1 comprises a group represented by a chemical structure general formula (2): # imgabs 1 # formula (2), in the formula (2), R2 comprises saturated long carbon chain substituents having different carbon atom numbers, and n is an integer of 1-3. M is a natural number greater than or equal to 0. According to the ceramic dressing provided by the invention, the binder with a specific structure is used, so that the ceramic dressing has strong adaptability to different electrolyte systems, and the problems of laser die cutting bead melting and the like can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a ceramic dressing, a tab, a battery core, a battery and an electrical device. Background Art

[0002] The main problems encountered by the tab ceramic coating in the battery cell manufacturing process include: after the battery cell is chemically divided into components, the bonding strength of the tab ceramic coating is severely attenuated with the infiltration of the electrolyte and high-temperature infiltration, and it is not adaptable to different electrolyte systems. The tab ceramic coating is prone to wrinkles or even falls off directly. In addition, after using conventional adhesives to improve the pain point of weak adhesion of the tab ceramic coating, abnormalities such as ceramic welding slag and melt beads are prone to occur during the laser die-cutting process. Therefore, it is more important to study ceramic coatings that have strong adaptability to different electrolyte systems and can effectively improve problems such as laser die-cutting melt beads. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one object of the present invention is to provide a ceramic dressing, which has strong adaptability to different electrolyte systems by using a binder with a specific structure and can effectively improve the problems such as laser die cutting molten beads.

[0004] The second object of the present invention is to provide a tab using the above ceramic dressing.

[0005] The third object of the present invention is to provide a battery cell using the above-mentioned tab.

[0006] A fourth object of the present invention is to provide a battery using the above-mentioned tab or battery cell.

[0007] A fifth object of the present invention is to provide an electrical device using the above-mentioned battery cell or battery.

[0008] The ceramic dressing according to the first embodiment of the present invention comprises a binder, wherein the binder comprises a compound having a chemical structural formula (1):

[0009] Formula (1) In formula (1), R1 includes a group having a chemical structure represented by formula (2):

[0010] Formula (2) In formula (2), R2 includes saturated long carbon chain substituents having different numbers of carbon atoms, and m is a natural number greater than or equal to 0.

[0011] According to the ceramic dressing of the first aspect of the present invention, the ceramic dressing also has strong resistance to electrolyte. The modified polyacrylic acid material is used as a binder, the bonding force is increased, and the adaptability to different electrolytes is strong. In different electrolyte systems, the bonding force of the tab ceramic coating is still outstanding. In addition, the increased bonding force of the binder can reduce the amount of binder used in the ceramic dressing, which can effectively improve problems such as laser die-cutting beads.

[0012] According to some embodiments of the present invention, the number of carbon atoms of the long carbon chain substituent is N, wherein N satisfies: 4≤N≤8.

[0013] According to some embodiments of the present invention, N is 4, 6 or 8.

[0014] According to some embodiments of the present invention, the long carbon chain substituent is a straight chain substituent.

[0015] According to some embodiments of the present invention, m is 0, 1, 2 or 4.

[0016] According to some embodiments of the present invention, the relative molecular weight of the compound represented by the chemical structural formula (1) is M, wherein M satisfies: 1000000≤M≤20000000.

[0017] According to some embodiments of the present invention, the ceramic dressing includes, by weight: 15 to 30 parts of the binder, 80 to 100 parts of boehmite, and 120 to 550 parts of a solvent.

[0018] According to some embodiments of the present invention, the solid content of the ceramic dressing is 20%-40%.

[0019] According to some embodiments of the present invention, the D 50 The specific surface area of ​​the boehmite is 1 g / m 2 -10g / m 2 .

[0020] According to some embodiments of the present invention, the boehmite includes modified boehmite, and the modified boehmite is prepared by performing activation modification treatment with a coupling agent and then melt-extruding the modified boehmite with a polymer material.

[0021] The electrode tab according to the second embodiment of the present invention comprises: a substrate, on the outer peripheral surface of which is coated the ceramic dressing according to the first embodiment to form a ceramic coating.

[0022] According to some embodiments of the present invention, the thickness of the ceramic coating is d, wherein d satisfies: 50 μm≤d≤150 μm.

[0023] The battery cell according to the third aspect of the present invention comprises the tab according to the second aspect of the present invention.

[0024] The battery according to the fourth aspect of the present invention comprises the tab according to the second aspect, or the battery cell according to the third aspect.

[0025] The electrical equipment according to the fifth aspect of the present invention comprises the battery cell according to the third aspect or the battery according to the fourth aspect.

[0026] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 is a graph showing the electrolyte compatibility test results of a ceramic dressing according to an embodiment of the present invention; Figure 2 1 is a graph showing the results of a laser die-cutting test of a ceramic dressing according to an embodiment of the present invention. DETAILED DESCRIPTION

[0028] The embodiments of the present invention are described in detail below. The embodiments described with reference to the accompanying drawings are exemplary. Figure 1 and Figure 2 The ceramic dressing according to the first embodiment of the present invention is described. In the following description of the present application, the ceramic dressing is coated on the surface of the positive electrode tab to form a ceramic coating for illustration.

[0029] The ceramic dressing according to the first embodiment of the present invention includes a binder.

[0030] Specifically, the binder includes a compound having a chemical structure represented by the general formula (1):

[0031] Formula (1) In formula (1), R1 includes a group having a chemical structure represented by formula (2):

[0032] Formula (2) In formula (2), R2 includes saturated long carbon chain substituents having different numbers of carbon atoms, and m is a natural number greater than or equal to 0.

[0033] For example, the binder is a modified polyacrylic acid material (also referred to as the modified PAA material below). That is, the main structure of the binder is polyacrylic acid (PAA), R1 is a grafted group, and the general chemical structure of the R1 group is shown in the above formula 2). R1 ​​is a structure having a double bond and a -COO- bond, and having a special structure of alkyl chains of different lengths, and R1 is a long carbon chain group with multiple carbon atoms.

[0034] For example, ceramic coatings using traditional binders such as PVDF (polyvinylidene fluoride) materials have poor electrolyte resistance because the CF bonds in PVDF react with aluminum foil (Al) to form van der Waals forces. The modified PAA material used in this application contains COOH to react with aluminum foil (Al) to form hydrogen bonds. In addition, the substituent group R1 contains alkyl chains of different lengths, unsaturated double bonds and ester bonds, which are similar to the structure of ethylene carbonate in the electrolyte. According to the principle of like dissolves like, the adhesion of the ceramic dressing with the binder of this application to the aluminum foil is significantly increased. In other words, a solute material (referring to the binder) similar to the structure of the electrolyte is used, and the ester COOR and other structures make its melting temperature reach 40-80°C. The lower the melting point, the smaller the intermolecular force, thereby avoiding the dissolution and destruction of the ceramic dressing by the electrolyte-related components, or avoiding the electrolyte-related components from weakening the adhesion of the ceramic dressing to the aluminum foil. That is to say, compared with traditional binders such as PVDF (polyvinylidene fluoride) materials, the modified PAA material has greater bonding strength and is more adaptable to different lithium salt-containing electrolytes. In different lithium salt-containing electrolyte systems, the tab ceramic coating (that is, the coating formed by the ceramic dressing coated on the aluminum foil) still has outstanding bonding strength. At the same time, the ceramic dressing can be applied to a variety of types of electrolytes, which also improves the performance of the ceramic dressing.

[0035] Take lithium salt electrolyte as an example. Lithium salt electrolyte is an electrolyte solution used in batteries (especially lithium-ion batteries). It is mainly composed of lithium salt, organic solvent and additives. Lithium salt is a kind of electrolyte solution used in batteries (especially lithium-ion batteries). + ), organic solvents are used to dissolve lithium salts, and additives are used to improve the various properties of the electrolyte. Common lithium salts include lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), etc. Organic solvents include ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), etc. These organic solvents are usually used in combination to achieve better performance.

[0036] In traditional technology, when the content of binder is too high, it will affect the effect of laser die cutting during welding, which is specifically manifested in the appearance of abnormal points such as burrs, welding slag and melt beads at the interface of the ceramic coating. The bonding force of the binder in this application is increased, so that the amount of binder used in the ceramic dressing can be reduced, which can effectively improve the problems such as laser die cutting melt beads. At the same time, the ceramic dressing also has strong resistance to electrolytes. "Laser die cutting" refers to setting appropriate laser die cutting parameters according to the size and shape of the lithium battery, including laser power, scanning speed, pulse frequency, etc.

[0037] According to the ceramic dressing of the first aspect of the present invention, the ceramic dressing also has strong resistance to electrolyte. The modified polyacrylic acid material is used as a binder, the bonding force is increased, and the adaptability to different electrolytes is strong. In different electrolyte systems, the bonding force of the tab ceramic coating is still outstanding. In addition, the increased bonding force of the binder can reduce the amount of binder used in the ceramic dressing, which can effectively improve problems such as laser die-cutting beads.

[0038] According to some embodiments of the present invention, the number of carbon atoms in the long carbon chain substituent is N, wherein N satisfies: 4≤N≤8. That is, the number of carbon atoms in the substituent R2 can be 4, 5, 6, 7 or 8. In this way, the length of the saturated long carbon chain substituent in the substituent R2 is moderate, which is conducive to improving the performance of the adhesive and increasing the ability of the adhesive to adhere to the aluminum foil. In addition, it is also conducive to the generation of the substituent R1, and then to the grafting of the substituent R1 on the polyacrylic acid.

[0039] Optionally, N is 4, 6 or 8. When N is 4, the substituent R2 is a n-butyl group, i.e., -CH2CH2CH2CH3. When N is 6, the substituent R2 is a n-hexyl group, i.e., -CH2CH2CH2CH2CH2CH3. When N is 8, the substituent R2 is a n-octyl group, i.e., -CH2CH2CH2CH2CH2CH2CH3. Of course, the long carbon chain substituent can also be a branched structure. The alkyl chain usually affects the movement of the polymer material chain. As the alkyl chain increases, the molecular weight of the compound increases, and the corresponding polymer flexibility is improved. At the same time, combined with the limitation of the relative molecular weight of the compound shown in the chemical structure formula (1), the performance of the binder can be effectively improved. For example, the structural formula of the substituent R2 with different carbon atom numbers is shown in the following formula (3).

[0040] Formula (3) According to some embodiments of the present invention, the long carbon chain substituent is a straight chain substituent.

[0041] In this way, the linear long carbon chain substituents usually have a longer carbon chain length, which makes them more flexible. Carbon chains can bend and rotate freely to a certain extent to adapt to different environments and intermolecular interactions. Flexible long carbon chain substituents can affect the conformation and morphology of molecules. For example, in polymers, long carbon chain substituents can adjust the chain structure of polymers by changing their own conformation, thereby affecting the performance of polymers. That is, the linear substituents make the binder flexible, so as to facilitate the infiltration of the ceramic coating electrode containing the flexible binder in the electrolyte. In addition, linear long carbon chain substituents usually have higher chemical stability, which is due to the high bond energy of carbon-carbon single bonds and is not easy to break. In addition, the linear structure makes the interaction between molecules more uniform, reducing local stress and instability factors. Chemical stability allows compounds containing linear long carbon chain substituents to remain stable under some harsh environmental conditions. For example, under conditions of high temperature, high pressure, strong acid, strong alkali, etc., linear long carbon chain substituents may be relatively difficult to decompose or react, thereby improving the stability of ceramic dressings.

[0042] According to some embodiments of the present invention, m is 0, 1, 2 or 4. For example, when m is 0, 1, 2, 4, respectively, R1 is a group having the chemical structural formula (4), (5), (6), (7), respectively:

[0043] Formula (4)

[0044] Formula (5)

[0045] Formula (6)

[0046] Formula (7) The presence of the above different alkyl chain lengths and double bond structures further endows the modified binder with flexibility. The presence of acrylic acid and ester groups endows the binder with adhesiveness. The specific components of the above binders can be detected by elemental analyzers, Fourier infrared detection, nuclear magnetic resonance and other technical methods to detect specific group types at the ceramic coating interface of the tab.

[0047] According to some embodiments of the present invention, the relative molecular weight of the compound represented by the chemical structure formula (1) is M, wherein M satisfies: 1000000≤M≤20000000. The main structure of the binder of the present application is polyacrylic acid material, and the degree of polymerization n in formula (1) determines the molecular weight of the material. From the perspective of weight average molecular weight, the molecular weight M of the binder is controlled between 1 million and 20 million, which can give it flexibility, thereby reducing its glass transition temperature.

[0048] According to some embodiments of the present invention, the ceramic dressing includes, by weight: 15 to 30 parts of a binder, 80 to 100 parts of boehmite, and 120 to 550 parts of a solvent.

[0049] Boehmite, also known as soft water stone, has a molecular formula of γ-AlOOH (hydrated aluminum oxide). For example, the solvent is NMP (N-methylpyrrolidone). Boehmite is used as a ceramic dressing on the tab. Boehmite has good insulation properties and can effectively prevent short circuits between tabs or between tabs and other components, reduce the safety risks of batteries caused by short circuits, and improve the overall safety of batteries. Inside the battery, the tabs will come into contact with the electrolyte. Boehmite has good compatibility with the electrolyte and will not undergo violent chemical reactions with the electrolyte, thereby ensuring the stability of the battery during long-term use. At the same time, good compatibility also helps to improve the wettability of the electrolyte on the surface of the tab. In addition, the chemical environment inside the battery is relatively complex, and there are various corrosive substances. Boehmite has strong corrosion resistance and can resist the erosion of these corrosive substances, protect the tabs from damage, and extend the service life of the tabs. In addition, by adopting the above-mentioned ratio, the ratio of binder to boehmite is moderate, and the ratio of binder to boehmite is also moderate, so that the ceramic dressing can fully exert the characteristics of boehmite, such as low thermal expansion coefficient, high hardness, etc., while maintaining a certain bonding force. In addition, the appropriate ratio helps the ceramic dressing to be evenly coated on the aluminum foil substrate, forming a stable ceramic coating and improving the quality of the ceramic coating. For example, the amount of binder added to boehmite can be controlled within the range of 15-25%.

[0050] According to some embodiments of the present invention, the solid content of the ceramic dressing is 20%-40%. For example, when the solid content of the ceramic dressing is less than 20%, the low solid content of the ceramic dressing may weaken the bonding force between the ceramic dressing and the surface of the tab, and the ceramic dressing is easy to fall off or peel off from the tab during battery production, assembly or use. As a result, not only will the structural integrity of the tab be affected, but problems may also occur in the circuit connection inside the battery, thereby affecting the performance and safety of the battery. Moreover, the low solid content of the ceramic dressing may make it difficult for the ceramic dressing to form a uniform coating during the coating process, thereby affecting the safety performance of the battery and the service life of the tab.

[0051] When the solid content of the ceramic dressing is higher than 40%, the viscosity of the ceramic dressing may increase significantly due to the high solid content of the ceramic dressing, resulting in poor fluidity, making it difficult for the ceramic dressing to be evenly spread on the surface of the pole ear during the coating process, and problems such as uneven coating thickness, caking or flow marks are prone to occur, affecting the quality and consistency of the pole ear coating, which may have an adverse effect on the performance of the battery. In addition, a higher solid content of the ceramic dressing may increase the brittleness of the coating formed by the ceramic dressing. During the use of the battery, the pole ear will be subjected to a certain degree of mechanical stress such as bending and stretching. The ceramic dressing coating with greater brittleness is prone to cracking and peeling. Once the ceramic dressing is damaged, the conductivity and structural stability of the pole ear may be affected, thereby affecting the overall performance and reliability of the battery, and also increasing safety risks such as internal short circuits in the battery. In addition, ceramic dressings with high solid content may require more raw materials to prepare, which will directly lead to an increase in raw material costs. Therefore, setting the solid content of the ceramic dressing within the range of 20%-40% not only ensures the safety and overall performance of the battery, but also reduces the cost of the ceramic dressing.

[0052] According to some embodiments of the present invention, the D 50 The specific surface area of ​​boehmite is 0.3μm-10μm, and the specific surface area of ​​boehmite is 1g / m 2 -10g / m 2 .

[0053] When boehmite D 50 When the particle size is below 0.3 μm, the boehmite particle size is too small, the specific surface area between particles increases, and the surface energy is high, which makes it easy for the particles to attract each other and agglomerate. This makes it difficult to evenly disperse the boehmite during the application process. For example, in ceramic dressings, uneven coating may occur, affecting the consistency of the diaphragm performance, and thus adversely affecting the charge and discharge performance and cycle life of the battery. Moreover, the smaller particle size makes the Brownian motion of the boehmite particles in the liquid more intense. During the filtration or separation process, these fine particles can easily pass through the filter membrane or block the filter pores, resulting in reduced filtration and separation efficiency, and increasing the difficulty of operation and time cost in the production process.

[0054] When boehmite D 50 When the particle size is higher than 10μm, due to the larger particle size, larger particles may cause blockage or discontinuous coating during the coating process, affecting the processing quality and production efficiency of the pole piece. At the same time, in the subsequent battery assembly process, larger boehmite particles may also have a certain impact on the assembly accuracy of the battery, increasing the difficulty of assembly. In addition, during the operation of the battery, especially under some extreme conditions (such as overcharging, overheating, etc.), larger boehmite particles may not be able to effectively play a role in heat insulation and flame retardancy, increasing the risk of thermal runaway of the battery. Therefore, the D50 Setting it within the range of 0.3μm-10μm not only ensures the charge and discharge performance and cycle life of the battery, but also improves the safety performance of the battery.

[0055] When the specific surface area of ​​boehmite is less than 1 g / m 2 When the specific surface area of ​​boehmite is too small, there are fewer surface sites available for adsorption, which leads to a decrease in the adsorption capacity of reactants or adsorbates, affecting its catalytic efficiency or adsorption capacity. Moreover, a small specific surface area will reduce the contact area and interaction opportunities between boehmite and other substances in the surrounding environment, which may affect its bonding strength and compatibility with binders, electrolytes, etc. This may lead to a decrease in the stability of the coating layer, and problems such as shedding and stratification may occur during long-term use, thereby affecting the performance and service life of the battery. In addition, a smaller specific surface area may change the interaction force between boehmite particles, such as van der Waals forces, which may be relatively enhanced, resulting in particles being more easily agglomerated in the application system. Poor dispersibility makes it difficult for boehmite to be evenly dispersed in the matrix material, which may cause the local boehmite content to be too high or too low, affecting the uniformity and stability of the overall performance of the material.

[0056] When the specific surface area of ​​boehmite is greater than 10 g / m 2 When the boehmite particles with a large specific surface area are used, they may agglomerate more easily during processing, resulting in poor dispersibility. This will bring difficulties to the slurry preparation and coating process, affecting production efficiency and product quality. In addition, boehmite with a large specific surface area may require more binders to ensure its adhesion stability on the surface of the diaphragm, but too much binder may affect other performance of the battery, such as increasing the internal resistance of the battery. At the same time, if the compatibility of boehmite and the binder is not good, the ceramic coating may fall off, crack, and other problems during the long-term use of the battery, affecting the safety and service life of the battery. In addition, under normal circumstances, the preparation of boehmite with a large specific surface area may require more complex processes and higher technical requirements, which may lead to increased production costs. Therefore, the specific surface area of ​​​​boehmite is set at 1 g / m 2 -10 g / m 2 Within the range, the catalytic efficiency of boehmite is guaranteed, the safety and service life of the battery are improved, and the production cost is reduced. For example, the structural integrity of the tab is improved, which is beneficial to current collection. In addition, the integrity of the ceramic dressing coating is beneficial to safety and can prevent short circuits. Aluminum foil defects on the surface or cross-section of the tab will affect the puncture of the diaphragm. It should be noted that the structural characteristics of the boehmite material in the formula design involved in this application are not limited to the above particle size range values ​​and specific surface area analysis.

[0057] According to some embodiments of the present invention, boehmite includes modified boehmite, which is prepared by using a coupling agent for activation and modification, and then melt-extruding the modified boehmite with a polymer material. The molecular formula of the modified boehmite is as shown in formula (8): R3-γ-AlOOH Formula (8).

[0058] For example, boehmite is activated and modified with a coupling agent such as phthalate, and then melt-extruded with a polymer material such as polytetrafluoroethylene (PTFE), polytetrafluoroethylene (PVDF), and polyurethane (PU) to obtain a modified boehmite material, collectively referred to as R3-γ-AlOOH.

[0059] Therefore, by filling the above-mentioned activated modified boehmite into a part of flexible polymer materials such as PTFE, PVDF, and PU through a melt blending method, the modified boehmite has a specific inorganic material with strong adhesion and flexibility, R3-γ-AIOOH, and its thermal stability is improved during the process. Based on this type of modified boehmite material, the poor electrolyte resistance of the tab ceramic coating and the defects of burrs and melt beads that are prone to occur in laser die cutting can be effectively solved.

[0060] The electrode tab according to the second embodiment of the present invention comprises: a substrate, on the outer peripheral surface of which is coated the ceramic dressing according to the first embodiment to form a ceramic coating.

[0061] The tab according to the embodiment of the present invention improves the performance of the tab and also improves the stability of the tab.

[0062] According to some embodiments of the present invention, the thickness of the ceramic coating is d, wherein d satisfies: 50μm≤d≤150μm. For example, if the thickness of the double-sided pole ear ceramic coating is easy to exceed 90μm, welding slag, burr beads and other phenomena will appear during the laser die-cutting process. For thick pole ear ceramic coating systems, its applicability is not strong. For the ceramic coating of the present application, because it has a certain flexibility, the ceramic coating pole piece has better flexibility when acting on the boehmite system, which has an advantage over high-added PVDF additives. The design adaptability of the pole ear ceramic coating is high for different thicknesses, which can meet the needs of different projects.

[0063] The battery cell according to the third aspect of the present invention comprises the tab according to the second aspect of the present invention.

[0064] According to the battery cell of the embodiment of the present invention, by adopting the above-mentioned pole tab, the performance of the pole tab is improved, which is conducive to the stable use of the pole tab.

[0065] The battery according to the fourth aspect of the present invention comprises the tab according to the second aspect, or the battery cell according to the third aspect.

[0066] The battery according to the embodiment of the present invention improves the performance of the battery by adopting the above-mentioned tabs or battery cells, which is beneficial to the long-term use of the battery.

[0067] The electrical equipment according to the fifth aspect of the present invention comprises the battery cell according to the third aspect or the battery according to the fourth aspect.

[0068] According to the electric equipment of the embodiment of the present invention, the use performance of the electric equipment is improved by adopting the above-mentioned battery cell or battery. For example, the electric equipment includes vehicles, aircraft, ships, computers, energy storage cabinets, etc.

[0069] Other structures and operations of the tabs, battery cells, batteries and electrical equipment according to the embodiments of the present invention are well known to those skilled in the art and will not be described in detail here.

[0070] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention. In addition, if not explicitly stated, all reagents used in the following embodiments are commercially available, or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0071] The binder and the battery of the present invention are described by means of exemplary specific examples and comparative examples. The following tests are performed on the ceramic dressings of Examples 1-2 and Comparative Examples 1-2 to determine the relevant properties.

[0072] The compatibility test method of the electrolyte for ceramic dressings is described as follows: Under a dew point control environment, the electrode coated with ceramic dressings is placed in a lithium salt electrolyte solution for immersion, and then immersed in a high temperature environment of 45°C. After immersion for 24 hours, the electrode is taken out to observe its surface state and adhesion to the aluminum foil. Figure 1 Left picture.

[0073] The viscosity test is carried out in accordance with GB / T 9751-1988.

[0074] The analysis and verification test methods for the feasibility of laser die cutting are as follows: In evaluating the feasibility of laser die cutting of different ceramic dressings, the focus is on evaluating the following two aspects: (1) the length of the vertical burr and the horizontal burr; (2) the size of the slag and molten bead diameter.

[0075] In detail, first ensure that the guide roller in front of the upper roller is clean, and place the positive electrode sheets prepared in different embodiments and comparative examples on the guide roller. The parameter details of welding equipment such as lithium battery laser die-cutting machine are as follows: the pulse width is set to 60ns, the single pulse energy is between 0.2-0.4mj, the frequency is set to 30KHZ to 1000KHZ, that is, the minimum value is 30KHZ, the pole piece tape speed is set to 650mm / s, and the minimum speed is 200mm / s. During the laser die-cutting process, it is particularly important to ensure that the pole piece tape speed can have a minimum speed. It is also critical to control the minimum speed at around 200mm / s, and ensure that the frequency is set at 30KHZ, which can reduce laser overlap and reduce the degree of energy concentration.

[0076] Example 1 (1) Prepare the binder solution: Add 3kg 15 parts of binder and NMP solution to obtain a binder solution with a solid content of 6%, and ensure that the viscosity of the binder solution is greater than 1000mpa.s. Keep stirring fully during the process to ensure that there is no obvious insoluble matter and particulate matter in the binder solution during the mixing and dispersion process with the boehmite material.

[0077] The binder is a compound having a chemical structure represented by the general formula (1), wherein R2 is -CH2CH2CH2CH3 and m is 4. (representing the polyacrylic acid material modified by the above C4 structure) (2) Preparation of ceramic dressing: The binder solution obtained in step (1) is continuously stirred in a stirring tank, and 18 kg, 90 parts of boehmite material is added during the stirring process. The boehmite can have a particle size of D 50 The surface area is 2.2 μm and 6.1 g / m 2 . After mixing, a ceramic dressing is obtained.

[0078] The ceramic dressing obtained above is coated on the positive electrode plate to carry out relevant performance test measurements.

[0079] Example 2 The main difference from Example 1 is that the binder is a compound having a chemical structure represented by the general formula (1), wherein R2 is -CH2CH2CH2CH2CH2CH2CH2CH2CH3, and m is 2. (representing the above-mentioned C8 structure-modified polyacrylic acid material) Comparative Example 1 The main difference from Example 1 is that the binder is a PVDF material, wherein, by weight, the ceramic dressing comprises 15 parts of PVDF material, 90 parts of boehmite, and 245 parts of NMP solvent.

[0080] Comparative Example 2 The main difference from Example 1 is that the binder is a PVDF material, wherein the ceramic dressing comprises 35 parts of PVDF material and 90 parts of boehmite by weight.

[0081] The lithium salt electrolyte used in the above-mentioned embodiments and comparative examples is specifically: the organic solvent is a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1, and the concentration of lithium hexafluorophosphate (LiPF6) in the electrolyte is 1 mol / L.

[0082] The test results of the above embodiments and comparative examples are shown in Table 1.

[0083] Table 1 Performance test results of ceramic dressings of Examples 1-2 and Comparative Examples 1-2

[0084] From Table 1 above, combined Figure 1 (in, Figure 1 DOE1 in the figure is the effect diagram of comparative example 1 under lithium salt electrolyte, The electrode piece fell off; DOE2 is the rendering of comparative example 2 under lithium salt electrolyte. The electrode piece did not fall off, nor did the electrode piece surface wrinkle, and the electrode piece had good adhesion to the aluminum foil; DOE3 is the rendering of Example 1 under lithium salt electrolyte). It can be seen that the electrode piece did not fall off, because the ceramic dressing prepared by the adhesive of the present application has strong adhesion and good electrolyte resistance. Comparative example 2 shows that the adhesion increases with the increase of PVDF material content, but as the PVDF material content increases, the thickness of the ceramic coating will fluctuate, and it is even easy to exceed the thickness control. However, the increase in coating thickness will affect the effect of laser die-cutting, such as the appearance of abnormal points such as burrs, welding slag and welding beads. The normal die-cutting effect diagram is as follows Figure 2 In Example 1 and Example 2, the die-cutting effect of the ceramic coated pole piece at different cross-section positions under the ultra-depth-of-field microscope was good, and no abnormalities such as burrs and welding slag occurred.

[0085] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0086] In the description of the present invention, "plurality" means two or more.

[0087] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0088] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A ceramic dressing, characterized in that: The invention comprises a binder, wherein the binder comprises a compound having a chemical structural formula (1): Formula (1) In formula (1), R1 includes a group having a chemical structure represented by formula (2): Formula (2) In formula (2), R2 includes saturated long carbon chain substituents having different numbers of carbon atoms, and m is a natural number greater than or equal to 0.

2. The ceramic dressing according to claim 1, characterized in that The number of carbon atoms of the long carbon chain substituent is N, wherein N satisfies: 4≤N≤8.

3. The ceramic dressing according to claim 2, characterized in that: The N is 4, 6 or 8.

4. The ceramic dressing according to claim 1, characterized in that: The long carbon chain substituent is a straight chain substituent.

5. The ceramic dressing according to claim 1, characterized in that: The m is 0, 1, 2 or 4.

6. The ceramic dressing according to claim 1, characterized in that: The relative molecular weight of the compound represented by the chemical structural formula (1) is M, wherein M satisfies: 1000000≤M≤20000000.

7. The ceramic dressing according to any one of claims 1 to 6, characterized in that: In parts by weight, the ceramic dressing comprises: 15 parts to 30 parts of the binder, 80 parts to 100 parts of boehmite, and 120 parts to 550 parts of a solvent.

8. The ceramic dressing according to claim 7, characterized in that: The solid content of the ceramic dressing is 20%-40%.

9. The ceramic dressing according to claim 7, characterized in that: The D of the boehmite 50 The specific surface area of ​​the boehmite is 1 g / m 2 -10g / m 2 .

10. The ceramic dressing according to claim 7, characterized in that: The boehmite includes modified boehmite, and the modified boehmite is prepared by performing activation modification treatment with a coupling agent and then melt-extruding the modified boehmite with a polymer material.

11. A tab, characterized in that: include: A substrate, the outer peripheral surface of which is coated with the ceramic dressing according to any one of claims 1 to 10 to form a ceramic coating.

12. The electrode tab according to claim 11, characterized in that: The thickness of the ceramic coating is d, wherein d satisfies: 50 μm≤d≤150 μm.

13. A battery cell, characterized in that: Comprising the electrode tab according to claim 11 or 12.

14. A battery, characterized in that: It comprises the electrode tab according to claim 11 or 12, or the battery cell according to claim 13.

15. An electrical equipment, characterized in that: Comprising the battery cell according to claim 13, or the battery according to claim 14.